Anticoagulant Therapy in Moderate to Severe COVID-19 Patients - Achmad, Agus Fitriyanto; Raharjani, Yuni Iswati; Setyaningrum, Zidni; Pramono, Bagus Andi; Selvyana, Dita Ria; Negoro, Sri Pramesthi Wisnu Bowo (Universitas Muhammadiyah Yogyakarta, 2022)
Coronavirus disease-19 (COVID-19) has a spectrum of severity from no symptoms to serious complications. Coagulopathy is a serious complication of COVID-19, and that condition is a marker of poor prognosis. Anticoagulant drugs are often used as prophylaxis and thrombosis therapy to treat COVID-19 patients. Anticoagulant therapy is indicated for moderate-severe COVID-19 patients. Low molecular weight heparin (LMWH) and Unfractionated Heparin (UFH) are anticoagulant drugs of choice for prophylaxis and thrombosis therapy in COVID-19 patients. When administering anticoagulant drugs, monitoring bleeding, renal function, and platelet count needs to be done, even if only as thromboprophylaxis. LMWH and UFH have good clinical efficacy with minimal side effects in managing COVID-19 patients.